Transformational leadership, pedagogical competence, deep learning, and teachers' readiness for educational change - Yanti Azmaniar; Lusi Susanti; Rusdinal Rusdinal; Edwin Musdi (Journal of Educational and Learning Studies, 2026)
This study aimed to examine the effects of transformational leadership and teachers' pedagogical competence on deep learning implementation and teachers' readiness for change in public junior high schools in Padang Pariaman Regency. A quantitative explanatory design was employed using a survey of 228 teachers selected through proportionate stratified random sampling from a population of 557 teachers. Data were collected using a five-point Likert questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). Pedagogical competence exerted the strongest positive effect on deep learning implementation (β = 0.720), followed by transformational leadership (β = 0.187). Both variables significantly influenced teachers' readiness for change directly and indirectly through deep learning implementation. The structural model demonstrated moderate-to-strong explanatory power (R² = 0.662–0.681). Strengthening teachers' pedagogical competence, supported by transformational school leadership, is essential for promoting effective deep learning implementation and enhancing teachers' readiness for sustainable educational change